Effect of hot rolling on microstructures and mechanical properties of Ni base superalloy. (April 2020) - Raza, Syed Shehzad; Ahmad, Tahir; Kamran, Muhammad; Zhang, Xuehui; Basit, Muhammad Abdul; Manzoor, Muhammad Umar; Inam, Aqil; Butt, Osama Majeed; Abrar, Muhammad
Abstract: Nickel-based superalloys have excellent mechanical properties at high temperature as well as they exhibit good corrosion resistance against organic and mineral acids. In view of their effectual physic-chemical nature, it was aimed to characterize nickel base superalloys casted by using vacuum induction furnace and subsequently hot rolled at 800 °C. Microstructural investigation and fracture mechanism of prepared alloy samples was carried out using optical and scanning electron microscopy (SEM), while elemental details were obtained through energy dispersive spectroscopy (EDX) analysis. Imperative mechanical characteristics including hardness and tensile behavior were studied using Micro-Vicker hardness tester etc. The resultant indentations were also studied under SEM and it was deduced that the hot rolling produced microstructure without any segregation of carbides at the grain boundaries. This advantageous outcome of deformation behavior credits better mechanical properties in it as compared to cast alloy. Highlights: Development and hot rolling of Ni base superalloy. Dendrite microstructure in cast alloy. Deformed dendrite microstructure in hot rolled alloy. Gamma (γ) and carbides phases in cast alloy. Improved mechanical properties due to Grain refinements and γ′ phase in hot rolled alloy.